SELECTIVE EXPOSURE TO PORNOGRAPHY AMONG THE TEENAGERS OF MODERN ISLAMIC BOARDING SCHOOL IN JAKARTA, INDONESIA - Inge Hutagalung (IJRDO - Journal of Social Science and Humanities Research, 2019)
At the beginning of his thinking, Festinger has placed the belief as a variable that causes selective exposure. Over time, many studies have explained that selective exposure is not only related to the belief variable. Recognizing that the study of causes of selective exposure has not reached unanimity and tends to focus only on one variable or one aspect, and understand that communication behavior must be comprehensively (holistically) from various aspects, both self (personal), message and social, Hutagalung (2018) conducted a study of selective exposure about pornography among teenagers in Jakarta, by integrating and seeing the influence of the three aspects that have been studied in the study of selective exposure in a model. Research conducted by Hutagalung (2018) shows that in an integrated belief variable, the usefulness of information and group support has an influence on selective exposure. Based on the theoretical model tested, it is known that the usefulness of information variables has a stronger influence than the group support variable and belief in selective exposure. The belief variable has the weakest influence on selective exposure. The question arises regarding the research conducted by Hutagalung (2018), what if the testing of this theoretical model is carried out among adolescent Islamic boarding school. Will the variable utility of information have the strongest influence? Will the belief variable have the weakest influence? This is interesting to observe considering that parenting in Islamic boarding school has a parenting model that is subject to the rules of Islamic boarding school. Hypothesis testing of this study was carried out by Structural Equation Modeling, with the results of research that showed that the belief variable had the strongest influence on selective exposure about pornography compared to the variable utility of information and group support.